Diverse carbonous nanocomposites of Ce2Y2O7 for boosting hydrogen storage capacity; Synthesis, characterization and electrochemical studies. (July 2023) - Khaksar, Mandana; Jasim, Layth S.; Mahdi, Makarim A.; Abdulsahib, Waleed K.; Mousavi-Kamazani, Mehdi; Salavati-Niasari, Masoud
Abstract: Carbon based materials due to high conductivity can provide the best conditions for energy storage through electrochemical process. Especially, nanosized carbon materials with active sites can participate in the hydrogen storage process along with metal oxide compounds. This work focuses on the hydrogen storage ability of sol-gel synthesized Ce2 Y2 O7 nanoribbons as active materials. Effect of carbonous materials with different structures such as GO, N-GQDs and g-C3 N4 were compared on the hydrogen storage capacity of Ce2 Y2 O7 nanoribbons. The provided carbonous nanocomposites were characterized using different methods in terms of identification of phase purity, shape and porosity. The galvanostatic charge-discharge profiles for all samples performed for achieving ideal capacitance. The results illustrate the maximum discharge capacity of 656, 686 and 757 mAhg −1 for nanocomposites of GO/Ce2 Y2 O7, N-GQDs/Ce2 Y2 O7 and g-C3 N4 /Ce2 Y2 O7, respectively while the pristine Ce2 Y2 O7 nanoribbons have discharge capacity of 643 mAhg −1 after 15 cycles. Graphical abstract: Unlabelled Image Highlights: Synthesis of Ce2 Y2 O7 nanoribbons by solution combustion method Design carbonous nanocomposites with GO, N-GQDs and g-C3 N4 materials Comparing the hydrogen storage capacity of carbonous nanocomposites against pristine Ce2 Y2 O7 The best performance is related to the nanocomposites of g-C3 N4 /Ce2 Y2 O7 .